The Factors Impact On Earnings Management On Indonesia Mining Company - Martinus Robert Hutauruk; Agus Riyanto; Greacela Utami Putri (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2022)
This purpose of this research to analyze the impact of size, age, profitability, and leverage on earnings management of the company. The data sampling was selected using a purposive sampling technique to obtain 20 mining companies listed on the Indonesia Stock Exchange IDX that can meet the criteria. The analysis in this study was binary logistic regression analysis through SPSS 26. The analysis found that firm size insignificant effect on earnings management. Company age has a negative and significant impact, profitability has no significant effect, and leverage insignificant effect on firm earnings management.